Inovasi Perancangan Manajemen Rantai Pasok "One Door" pada Pengrajin VCO di Kemranjen, Banyumas, Jawa Tengah - Anita Suri; Tantry Febrinasari (Prosiding Sains dan Teknologi, 2022)
Virgin Coconut Oil (VCO) is one of the products extracted from fresh-old-coconut using a simple method without the addition of synthetic chemicals and high heat. VCO is known as a functional oil as it has many health and beauty benefits. Kemranjen Subdistrict, located in Banyumas Regency, Central Java, is one of the VCO producing areas. However, most of the VCO craftsmen still face problems related to the low level of sales and consumer acceptance due to the quality of VCO products which are easily damaged during storage and distribution and the lack of consistency in the quality and quantity of the products because of the vary and uncertain raw materials from suppliers. One of solutions that can be applied is the "One Door" supply chain management design. This research is carried out by the survey method with MSME VCO in Kemrajen, Banyumas as the object of research. The sampling technique used in this study is the purposive sampling method. The initial stage of implementing the "One Door" supply chain management is to directly analyze the problems faced by the Kemrajen VCO Craftsmen, then provide solutions with the "One Door" system. The "One Door" system covers upstream (raw materials) to downstream (the products reach the consumers) processes, including: raw materials (grouping based on coconut grade); production and final products (grouping based on final product grade) with barcode system storage, distribution of products using FIFO (First One First Out) system; sales and marketing (grouping of consumer types). This system is expected to increase the quality and quantity of VCO products that can benefit producers and consumers. Keywords: VCO, VCO craftsmen, Supply Chain Management, One Door